IS COMMUNICATING MATHEMATICS PART OF THE EASE OF ONLINE LEARNING FACTOR? - Eka Fitria Ningsih; Sugiman Sugiman; C. Asri Budiningsih; Dita Surwanti (Jurnal Infinity, 2023)
In this study, we focus on self-disclosure, communicating mathematics, and infrastructure support in determining the ease of online learning for students of mathematics education study programs. The sample in this study were students (n=465) who were asked voluntarily to fill out an online questionnaire. Participants consisted of 335 female students (72%) and 130 male students (28%) from various universities in Indonesia. The data were analyzed quantitatively using structural equation modeling. The results of the path analysis show that the ease of online learning is influenced by self-disclosure, communicating mathematics, and infrastructure support. The R square results show that these factors influence 47%. Each path analysis shows that self-disclosure (r = 0.556 p= 0.000) and infrastructure support (r = 0.243 p = 0.000) have a significant positive relationship with the ease of online learning. Meanwhile, communicating mathematics (r = -0.025 p =0.507) has an insignificant negative relationship to the ease of online learning. Further research is needed to see how the impact of mathematical application support communicating mathematics in online learning.